Strategi bauran pemasaran lembaga pendidikan Islam: Studi situs di Madrasah Ibtidaiyah An-Nuroniyah Rembang - Zainabiyyi, Syafiqoh Zuhda Samiyah; Muflikhah, Ayu Na'imatul; Asiska, Enda Saputra Sri; Lely, Fatimah Nur; Zuhriyah, Indah Aminatuz (Maliki Interdisciplinary Journal, 2024)
This article discusses the education marketing mix strategy which is the key to the success of educational institutions at Madrasah Ibtidaiyah An-Nuronniyah Rembang in facing the challenges of an increasingly competitive education market. The educational marketing mix involves a combination of marketing elements, including product, price, place, people, promotion, process, and physical evidence that can be used to achieve educational marketing objectives. The aim of this research is to explore various educational marketing mix strategies implemented at MI An-Nuronniyah Rembang that are effective in attracting the attention of prospective students, increasing the competitiveness of educ institutions, and building a positive image in society. The research method used involvesliterature study, data collection by interviews, and data analysis. Based on the research results, the marketing strategy implemented at Madrasah Ibtidaiyah An-Nuronniyah Rembang is through a mix of marketing strategies, namely by holding superior programs that are rarely found in other schools, strategic school locations, education costs that do not burden student parents, appropriate promotion targets, the presence of competent teaching staff in their fields, professional management of human resources, and no distinction between economic backgrounds in student admissions. By implementing various elements of the marketing mix strategy, MI An-Nuronniyah has succeeded in maintaining its existence to this day and is even recognized as a competitor for surrounding schools